2021
DOI: 10.1093/cid/ciaa1905
|View full text |Cite
|
Sign up to set email alerts
|

The Duration of Protection from Azithromycin Against Malaria, Acute Respiratory, Gastrointestinal, and Skin Infections When Given Alongside Seasonal Malaria Chemoprevention: Secondary Analyses of Data from a Clinical Trial in Houndé, Burkina Faso, and Bougouni, Mali

Abstract: Background Mass drug administration (MDA) with azithromycin (AZ) is being considered as a strategy to promote child survival in sub-Saharan Africa, but the mechanism by which AZ reduces mortality is unclear. To better understand the nature and extent of protection provided by AZ, we explored the profile of protection by time since administration, using data from a household-randomised, placebo-controlled trial in Burkina Faso and Mali. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…A trial in Burkina Faso and Mali found SMC + AZ provided additional protection from malaria, but this effect was limited to the rst two weeks post-administration. (19) Concomitant SMC distribution during the trial period may explain the lower than expected malaria prevalence we observed (8% RDT positivity at baseline and follow-up). (20-23) Community-level distribution of AZ could be more effective for malaria control compared to individuallevel as several community based trials have demonstrated that mass AZ distribution reduces malaria parasitemia.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…A trial in Burkina Faso and Mali found SMC + AZ provided additional protection from malaria, but this effect was limited to the rst two weeks post-administration. (19) Concomitant SMC distribution during the trial period may explain the lower than expected malaria prevalence we observed (8% RDT positivity at baseline and follow-up). (20-23) Community-level distribution of AZ could be more effective for malaria control compared to individuallevel as several community based trials have demonstrated that mass AZ distribution reduces malaria parasitemia.…”
Section: Discussionmentioning
confidence: 78%
“…Gastroenteritis and pneumonia were reduced 30% and 34% respectively in a West African azithromycin trial, suggesting AZ may lower other fever-inducing infections commonly found in sub Saharan Africa. (19,22) There were no other signi cant differences in other adverse events or clinic visits. Administration of azithromycin to preschool aged children appears to be safe and well tolerated.…”
Section: Discussionmentioning
confidence: 86%
“… 26 Secondary analysis of a trial of the mass administration of seasonal malaria prophylaxis plus azithromycin or placebo 27 showed no evidence of a protective effect of azithromycin on hospitalization and deaths, and protection from infectious illnesses was short-lived (2-4 weeks). 28 A trial in Niger is under way to test the effect of age-based targeting of biannual azithromycin on mortality and antimicrobial resistance in children. 29 …”
Section: Discussionmentioning
confidence: 99%
“…A household randomized trial of azithromycin versus placebo given alongside seasonal malaria chemoprevention for 3 consecutive years of administration in children aged 2 to 59 months showed no additional effect of azithromycin on malaria parasitaemia in Burkina Faso and Mali [ 21 ]. However, secondary analysis from this trial found a short-term reduction in rapid diagnostic test-confirmed malaria in children receiving azithromycin compared to placebo, confined to approximately 14 days post-treatment [ 22 ]. A study of biannual mass azithromycin distribution in Niger among children aged 1 to 59 months old found a nearly 50% reduction in the odds of malaria parasitaemia in children living in communities receiving azithromycin compared to placebo [ 3 ].…”
Section: Discussionmentioning
confidence: 99%